Long-term levodopa ameliorates sequence effect in simple, but not complex walking in early Parkinson's disease patients. (March 2023) - Ohara, Masahiro; Hirata, Kosei; Hallett, Mark; Matsubayashi, Taiki; Chen, Qingmeng; Kina, Satoko; Shimano, Kaoru; Hirakawa, Akihiro; Yokota, Takanori; Hattori, Takaaki
Abstract: Background: The sequence effect (SE) is characterized by the progressive decrement of movements and is often observed in Parkinson's disease (PD) patients. While acute effect of levodopa does not ameliorate the SE, the effect of long-term levodopa treatment for the SE remains unknown. Objective: We aimed to elucidate the SEs during various gait conditions and their response to long-term levodopa treatment in drug-naïve PD patients. Methods: Nineteen drug-naïve PD patients and 21 healthy controls were enrolled. Gait parameters were measured via wearable inertial sensors in the following conditions:1) straight walking, 2) circular walking: walking a circle of 1 m diameter in a clock-wise direction for 3 laps, 3) straight or circular walking under cognitive-motor dual-task (serial 7s subtractions). PD patients were evaluated at baseline, within 1 h after intravenous administration of levodopa, and after one, three, and six months treatment with levodopa. The SE was measured by a linear regression slope by plotting consecutive stride lengths over steps. Patients were also separately analyzed depending on laterality of symptoms. Results: Long-term levodopa treatment ameliorated the SE only during single-task straight walking. The SE during circular walking was exacerbated after long-term levodopa treatment for right-side dominant patients. During dual-task straight walking, the SE at baseline was greater in right-side dominant PD patients. Conclusions: The SE only during single-task straight walking can be ameliorated by long-term levodopa treatment. However, the SE may be exaggerated by cognitive motor interference or by asymmetrical stride length with/without long-term levodopa treatment, depending on the laterality of symptoms. Highlights: Long-term levodopa can improve the sequence effect in Parkinson's disease patients. The improvement in the sequence effect depends on the gait conditions. The sequence effect may be exaggerated by asymmetrical stride length. The sequence effect may be exaggerated by cognitive motor interference.